Structure of the dengue virus helicase/nucleoside triphosphatase catalytic domain - Xu, Ting (2008)
Infectious diseases caused by flaviviruses are important emerging public health concerns and new vaccines and therapeutics are urgently needed. The NS3 protein from flavivirus is a multifunctional protein with protease, helicase and nucleoside 5' triphosphatase activities (NTPase). Thus, NS3 plays a crucial role in viral replication and represents an interesting target for the development of specific antiviral inhibitors. This thesis reported the structure of an enzymatically active fragment of the dengue virus NTPase/ helicase C-terminal catalytic domain. The structure is composed of three domains, bears an asymmetric distribution of charges and comprises a tunnel large enough to accommodate single strand RNA. A concave face formed by domains 2 and 3 is proposed to bind a nucleic acid duplex substrate. Comparison of the various copies of dengue and yellow fever virus NS3 NTPase/helicase catalytic domains reveals mobile regions of the enzyme. Such dynamic behaviour is likely to be coupled with directional translocation along the single strand nucleic acid substrate during strand separation.